In the footsteps of Covid-19 convalescence - Alfredo Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
The proposal to extend the negative consequences of infection with the SARS-CoV-2 virus observation to two or three years is considered reasonable, by lengthening the follow-up time of a previously unknown condition. This communication' purpose is to provide new considerations about a fact: there are people who have not fully recovered, in a reasonable time, after having suffered from COVID-19. It is emphasized that we are still far from knowing all the biological effects that the "massive immunostimulation" of the pandemic will have over time on some people. Some practical recommendations are proposed, such as a) Include the information of having suffered from COVID-19 in the patients' personal pathological history; b) Insist on periodic monitoring of patients, especially those who express complaints of prolonged convalescence. Other consequences, in addition to the purely biological ones, are also important, including: mental, social, labor, economic, consumption of health services and social services. In relation to post-COVID, the challenge will always be linked to the application of effective strategies for the COVID-19 prevention and control. But if illness people appear, the challenge will be to avoid the possible causes of post-COVID, as well as prevent or mitigate the appearance of its different clinical forms with coherent behaviors, depending on the characteristics of each case, as well as mitigate, by all, the consequences that have been caused to the affected people and to society.